Recruitment to sheltered employment: Evidence from Samhall, a Swedish state-owned company - Per Skedinger; Barbro Widerstedt (Institute for Labour Market Policy Evaluation (IFAU), 2003)
This paper analyses recruitment practices to Samhall, a state-owned company that provides sheltered employment for individuals with severe work disabilities. Besides providing employment for disabled workers and rehabilitating them to employment outside Samhall, the company is expected to decrease its dependence on Government subsidies. This profitability goal may come into conflict with the recruitment goals, resulting in cream skimming effects. The job security offered at the company may also provide incentives at the individual level for using Samhall as a means of escaping unemployment rather than as an employer of last resort for the most disabled. The evidence regarding cream skimming is mixed; the recruitment-to-Samhall hazards of the prioritised groups, i.e., individuals with intellectual or psychic disabilities, are significantly higher than the hazards for some, but not all, disability groups. Individuals without disabilities tend to be hired by the company, which suggests creaming and is contrary to the guidelines. Finally, the Samhall hazard increases slightly with time in unemployment. This is consistent both with Samhall acting as an employer of last resort and the existence of incentives among individuals to use Samhall in order to escape unemployment.
Keywords: I12; J23; J24; J45; 330; Policy programmes; disability; performance standards